STUDIES IN CARBOTRICATIONS: PREPARATION AND CARBON-13 NUCLEAR MAGNETIC RESONANCE SPECTROSCOPIC STUDY OF 3,7,9-TRIHYDRO TETRACYCLO [3.3.1. 0 . 0 ] NONANE-3,7,9 TRIYLTRICATION: A TRIPROTONATED TETRACYCLO-[3.3.1.0 . 0 ] NONANE-3,7,9-TRIONE AND ATTEMPTED PREPARATION OF RELATED TRICATIONS (Journal of Sciences, Islamic Republic of Iran)
Synthetic approaches have been described for the preparation of precursors to triasterane trications and related carboxenium ions. The investigation on carbocationic intermediates from treatment of these precursors with FSO H/SbF /SO CIF system has led to the preparation and 13C-NMR spectroscopic characterization of the isomeric 3,7,9-tri-hydrote-tracyclo [3. 3.1. 0 . 0 ] nonane-3,7,9-triyltrications.